Bone and joint mycobacterial infection: a retrospective review of cases presenting to a UK district hospital. Issue 12 (December 2018) - Everden, A.; Mamo, J. P.; Somasunderam, D.; McKee, A.; Brij, S. O.; Enoch, D. A.
Abstract : Purpose. : Peterborough has one of the highest rates of tuberculosis (TB) in the east of England. We reviewed the epidemiology, management and outcome of all cases of bone and joint TB (BJTB) diagnosed since 2000. Methodology. : Retrospective review of all adult cases of BJTB between 1 January 2000 and 31 December 2015. Patients' notes were reviewed with regard to their presentation, investigation, management and outcomes. Results. : In total, 21 patients diagnosed with BJTB were reviewed. Thoracic and lumbar spine were the most common sites affected (62 %). The most common clinical manifestations included localized pain (76 %), fever (53 %) and weight loss (48 %). Fourteen (67 %) patients had a bone biopsy or aspirate sent for microbiological investigation; none were smear‐positive, but 11 were culture‐positive. Eleven patients (77 %) were fully susceptible to anti‐tuberculous drugs, one was isoniazid‐resistant and one was pyrazinamide‐resistant. Anti‐tuberculous therapy was given for 6‐16 months. Nineteen (90 %) patients completed therapy. Conclusions. : BJTB requires a high index of clinical suspicion. BJTB should be considered in any patient with unexplained pain, fever and weight loss. The diagnosis is proven by aspiration and biopsy and should be undertaken as soon as possible for culture purposes, as microscopy alone can be negative.